Peran Tuhan dalam Ritual Perkawinan Adat Guyub Tutur Manggarai: Kajian Linguistik Kebudayaan - Erfiani, Yohanes Paulus Florianus; Goreti Djehatu, Maria; Mario Bajo, Simforianus (Humanis, 2025)
This research is conducted to find out, describe, and narrate the God’s role which contained in the traditional marriage discourse of Manggarai speech community.Therefore, this research applied cultural linguistic perspective in analyzing the God’s role in traditional marriage discourse of Manggarai speech community. The cultural linguistic theory is combined with the qualitative research method. Moreover, this research is conducted in Cibal district, Manggarai regency, East Nusa Tenggara province. Thus, based on the source of the data, it can be concluded that God has the important role in conducting traditional marriage ritual of Manggarai speech community in the perspective of cultural linguistic theory. The several roles of God are God is believed to be the highest being, God is believed to be the creator of the universe/world, God is believed to be a guide, protector, and grantor of wishes, and God is believed to have the same appearances as humans.